Earnings management v.s. board independence : a comparison between listed and non-listed companies. - Quek, Kian Leong. (2008)
This paper examines the relation between earnings management and board independence based on the following board characteristics: the proportion of outside directors, the presence of Chief Executive Officer (CEO) duality and the presence of Chief Financial Officer (CFO) on board. We further demonstrate that non-listed firms exhibit a higher level of earnings management than listed firms.